Media Pembelajaran Fisika Menggunakan Bahan Recycle untuk Meningkatkan Kreatifitas dan Motivasi Belajar - Wahyudi, Beri Agung; Jumadi, Jumadi; Eryant, Eryanti (UIN Sunan Gunung Djati Bandung, 2024)
The utilization of instructional media is crucial in Physics education; however, several schools in remote areas lack practical tools as learning resources. The absence of these resources results in a lack of interest and motivation among students towards Physics learning. To address this issue, a project-based learning model is a suitable option, utilizing recycled materials as instructional media. The objective of this research is to demonstrate that incorporating recycled materials in a project-based learning model can enhance students' creativity and learning motivation. The research method employed is qualitative descriptive research. The findings of this study indicate that the effective use of recycled materials in a project-based learning model can improve students' creativity and learning motivation in the context of Physics education.